Metabolomics Reveal Induction of ROS Production and Glycosylation Events in Wheat Upon Exposure to the Green Leaf Volatile Z-3-Hexenyl Acetate - Ameye, Maarten; Van Meulebroek, Lieven; Meuninck, Bianca; Vanhaecke, Lynn; Smagghe, Guy; Haesaert, Geert; Audenaert, Kris (Frontiers in Plant Science, 2020)
The activation and priming of plant defense upon perception of green leaf volatiles (GLVs) have often been reported. However, which metabolic pathways in plants are affected by GLVs, remain elusive. We report the production of reactive oxygen species in the tip of young wheat leaves followed by an activation of anti-oxidant related enzyme activity. In this study, we aimed to uncover metabolic signatures upon exposure to the GLV Z-3-hexenyl acetate (Z-3-HAC). By using an untargeted metabolomics approach, we observed changes in the phenylpropanoid pathways which yields metabolites that are involved in many anti-oxidative processes. Furthermore, exposure to GLV, followed by an infection with Fusarium graminearum (Fg) induced significantly greater changes in the phenylpropanoid pathway compared to a sole Z-3-HAC treatment. Fragmentation of a selection of metabolites, which are significantly more upregulated in the Z-3-HAC + Fg treatment, showed D-glucose to be present as a substructure. This suggests that Z-3-HAC induce early glycosylation processes in plants. Additionally, we identified the presence of hexenyl diglycosides, which indicates that aerial Z-3-HAC is metabolized in the leaves by glycosyltransferases. Together these data indicate that the GLV Z-3-HAC is taken up by leaves and incites oxidative stress. This subsequently results in the modulation of the phenylpropanoid pathway and an induction of glycosylation processes.